"Anarquistas" e "servis": uma análise dos projetos políticos do ano de 1826 no Rio de Janeiro - Reis, Arthur Ferreira (2016)
The Brazilian's nineteenth century beginning was marked by the appearance of the first newspapers. They were created at the time of intense political turmoil caused by royal family's arrival as well as by the establishment of liberalism through Port Regeneration and by the independence process. In these times, these newspapers contributed to the strengthening of public opinion in Brazil. However, as long as the number of newspapers grew the repression of Brazilian public space actors that was carried forward by the government Pedro I ended up causing a decrease in public debate. Between 1824 and 1826, the number of newspapers in fluminense public scene was greatly reduced. During this period, especially in 1825, the group political aulic stood out as government supporters and entrepreneurs of a political language that sought to raise the Emperor as the higher Brazil's sovereign. However, if in 1825 they were able to take forward this project without major problems, in 1826 the fluminense press found out about the emergence of two opposition newspapers that stirred the political debate. In this process, authors and political factions, specifically the "anarchists" and "servile", vied for the support of the people, attacking his opponents and defending their political projects. Mindful of this, this search aims to study the political projects of newspapers Verdadeiro Liberal, Spectador Brasileiro and some interlocutor’s newspaper publications as Abelha de Itaculumy, Atalaia da Liberdade, Diário Fluminense, O Universal and O Triumpho da Legitimidade, plus three pamphlets published during 1826. The main objective of this search is to investigate the political projects served by these newspapers, supporting the existence of political language aulic and a radical project in Rio de Janeiro during the year 1826.